Investigating the Relationship between Students' Perceptions of English Songs and Measured Learning Outcomes - Jusak Patty; Cindy Itamar Latuihamallo; Hanafi Bilmona (Journal of Innovative and Creativity, 2025)
This study examines the correlation between students' perceptions of English songs and their English learning outcomes at SMK Negeri 1 Ambon. Employing a quantitative correlational design, the study involved 33 second-grade students from the Travel and Tourism Business department selected through simple random sampling. Data were collected using a Likert-scale questionnaire measuring students' perceptions of English songs' impact on six language skill areas while learning outcomes were assessed through semester English grades. The findings indicate that students hold highly positive perceptions of English songs as language learning tools (overall mean 3.95), with particularly strong ratings for listening (4.13), reading (4.10), vocabulary (4.07), and speaking (4.05) skills. While 87.9% of students achieved "Good" academic scores (80-89), preliminary normality testing necessitated non-parametric correlation analysis. Spearman's rank correlation coefficient (rs = 0.132, p = 0.466) revealed a very weak, statistically insignificant relationship between perceptions of English songs and learning outcomes. This disconnect can be interpreted through situated learning theory, suggesting that while songs create authentic language engagement, their benefits may not translate to standardized vocational assessments. The study contributes to understanding how the perceived benefits of English songs relate to academic performance in vocational education, suggesting that strategic integration of songs requires alignment with tourism-specific language competencies and assessment approaches.